2018
DOI: 10.1186/s13033-018-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Reforming the Portuguese mental health system: an incentive-based approach

Abstract: BackgroundTo promote an effective mental health system, the World Health Organization recommends the involvement of primary care in prevention and treatment of mild diseases and community-based care for serious mental illnesses. Despite a prevalence of lifetime mental health disorders above 30%, Portugal is failing to achieve such recommendations. It was argued that this failure is partly due to inadequate financing mechanisms of mental health care providers. This study proposes an innovative payment model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Previous research has shown that RNT is a transdiagnostic construct involved in emotional disorders such as generalized anxiety disorder, social anxiety, or major depression and is highly correlated with other transdiagnostic constructs such as worry and rumination (Arditte et al, 2016;Ehring & Watkins, 2008;Wahl, 2019). Furthermore, PINTS was significantly, negatively, and moderately correlated with life satisfaction, supporting the idea of an intrusive, repetitive, and negative thinking style as a burden on mental health and quality of life (Perelman et al, 2018). Interestingly, the current study found a stronger correlation between PINTS-PT and life satisfaction, by showing that Portuguese individuals who exhibited higher levels of persistent and repetitive negative thinking style, perceived greater impairment in their lives than individuals from the original study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous research has shown that RNT is a transdiagnostic construct involved in emotional disorders such as generalized anxiety disorder, social anxiety, or major depression and is highly correlated with other transdiagnostic constructs such as worry and rumination (Arditte et al, 2016;Ehring & Watkins, 2008;Wahl, 2019). Furthermore, PINTS was significantly, negatively, and moderately correlated with life satisfaction, supporting the idea of an intrusive, repetitive, and negative thinking style as a burden on mental health and quality of life (Perelman et al, 2018). Interestingly, the current study found a stronger correlation between PINTS-PT and life satisfaction, by showing that Portuguese individuals who exhibited higher levels of persistent and repetitive negative thinking style, perceived greater impairment in their lives than individuals from the original study.…”
Section: Discussionmentioning
confidence: 79%
“…In the Portuguese context, emotional disorders are very widespread (Antunes et al, 2018;WHO, 2017), which negatively affects the public mental health system and the quality of life of the population, leading to a high prevalence of the use of psychotropic drugs use (Perelman et al, 2018). The PTQ was translated and validated for the Portuguese population (Azevedo et al, 2017;Chaves et al, 2013), but failed to replicate the three-factor model of the original version (Ehring et al, 2011), suggesting a two-factor model (i.e., repetitive thoughts; and cognitive interference and unproductivity; Azevedo et al, 2017;Chaves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a different role of SPGH, other than the one investigated in this study, in the triad of SPGH, depression and functional status. These findings are relevant, given that depression is prevalent among older adults, being particularly high in Portugal in comparison with other European countries (Perelman et al, 2018). Further investigation in order to disentangle the contextual associations among these factors is of utmost importance and the results have the potential to inform decision makers with regards to healthy ageing.…”
Section: Discussionmentioning
confidence: 90%
“…Research in health inequalities among older adults have primarily focused on socio-economic determinants, such as educational level (Mackenbach et al, 2008;Campos-Matos et al, 2016;Uccheddu et al, 2019) and wealth (Ploubidis et al, 2012;Uccheddu et al, 2019), whereas gender differences and psycho-social determinants have been overlooked. This is surprising, because the role of psycho-social factors in reducing health inequalities irrespectively of age groups has been increasingly recognised (Stansfield and Bell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Possible barriers include inadequate screening, inability to tackle demand and/or insufficient collaborative care [ 28 ]. In Portugal, these may reflect conservative rates, since the country has one of the highest prevalence of CMD’s (23%) in Europe, representing the second largest cause of disability in the country, while access to mental health care is still below other European countries [ 29 , 30 ]. Furthermore, access to care is expected to decline due to the pandemic and its consequences on patients and services.…”
Section: Introductionmentioning
confidence: 99%